2002
DOI: 10.1051/vetres:2002049
|View full text |Cite
|
Sign up to set email alerts
|

Nematophagous fungi as a biological control agent for nematode parasites of small ruminants in Malaysia: a special emphasis on Duddingtonia flagrans

Abstract: -Approximately 2 800 fresh dung samples from animals, mainly ruminant livestock, were screened for the presence of nematophagous fungi in Malaysia. Arthrobotrys spp. was noted on numerous occasions, but only one isolate of Duddingtonia flagrans was made. For the purposes of producing sufficient quantities of this fungus for feeding trials in sheep, various, commonly available, cheap plant materials were tested as possible growth substrates. This showed that cereal grains (wheat, millet and rice) were the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 17 publications
0
13
0
3
Order By: Relevance
“…flagrans showed higher predatory activity on S. papillosus. Experiments with other D. flagrans isolates had already demonstrated the high predatory effectiveness of this species on H. contortus L 3 (Mendoza- Chandrawathani et al 2002).…”
Section: Resultsmentioning
confidence: 98%
“…flagrans showed higher predatory activity on S. papillosus. Experiments with other D. flagrans isolates had already demonstrated the high predatory effectiveness of this species on H. contortus L 3 (Mendoza- Chandrawathani et al 2002).…”
Section: Resultsmentioning
confidence: 98%
“…In Malaysia, Chandrawathani et al (2002) observed the effectiveness of the treatment with the fungus D. flagrans, daily administered to ovine. On the other hand, Terril et al (2004), using this same fungus, found a The number of (L 3 ) recovered from the paddocks in the distances of up to 20 cm from the fecal mass and 20-40 cm far from the fecal mass was similar (p>0.05) for the animals in groups 1, 2, and 3 in the months when the experiment took place.…”
Section: Discussionmentioning
confidence: 99%
“…D. flagrans were noted in 13 feces, 10 dung compost and 1 pasture soil samples, and 11 pure isolates were recovered. Detection of D. flagrans in China, following its isolation in continental Europe , Australia , North and South American continents , South Africa , and Malaysia and India in Asia, provides further support that this fungus is distributed worldwide. These findings also provide the opportunity to compare local fungi with strains from other locations regarding their efficacy in reducing infective parasitic larvae on pastures.…”
Section: Discussionmentioning
confidence: 79%